Polyhydroxyalkanoate recovery and effect of in situ extracellular polymeric substances removal from aerobic granules. (August 2015) - Gobi, K.; Vadivelu, V.M.
Highlights: PHA recovery methods from aerobic granules were evaluated for the first time. Sodium hypochlorite method produced the highest PHA recovery yield. EPS removal found to be influential in PHA recovery from aerobic granules. Highest PHA recovery produced when EPS was completely removed. Degradation of PHA was minimal with sodium hypochlorite dispersion method. Abstract: Polyhydroxyalkanoate (PHA) recovery from aerobic granules was investigated using four cell digestion agents, namely, sodium hypochlorite, sodium hydroxide, acetone and sodium chloride. Simultaneously, the removal of extracellular polymeric substances (EPS) and its effect on PHA yield were investigated. The highest PHA recovery yield was obtained using sodium hypochlorite, accounting for 89% cell dry weight (CDW). The highest PHA was recovered after the sodium hypochlorite completely removed the EPS from the aerobic granules. The average molecular weight ( Mw ) of the PHA recovered using sodium hypochlorite was 5.31 × 10 5  g/mol with only 1.8% molecular weight degradation. The energy and duration analysis for PHA recovery revealed that the sodium hypochlorite method required the least amount of energy and time at 0.0561 MJ/g PHA and 26 h, respectively. The PHA that was recovered was a P3(HB-co-HV) co-polymer.